Awareness of antimalaria policy and use of Artemisinin-based combination therapy for malaria treatment in communities of two selected local government areas of Ogun State, Nigeria (2014)
With limited data on the awareness of change in the use of antimalaria drugs and availability and use of artemisinin-based combination therapy (ACT) in the context of the Roll Back Malaria (RBM) program, we conducted the descriptive cross-sectional study of 262 registered women attending antenatal clinics and 233 mothers of under-five children. We used a questionnaire to assess the awareness, availability and the use of ACT in Ijebu North and Yewa North Local Government Area (LGAs) of Ogun State. Malaria is holo-endemic in these areas, and the RBM program has been implemented for years prior to the 2010 RBM deadline. Data were also collected through focus group discussions, along with secondary data from hospital records. Hospital stock records showed inadequate and inconsistent supplies of ACT drugs in hospitals surveyed. Only 23.0% of respondents knew about Act drugs. About 48% preferred analgesics over ACT drugs (0.6%) for malaria treatment. Lack of awareness was the major reason for non-use of ACT drugs (86.1%). Communities in Yewa North had more supplies of ACT drugs and knew more about ACT than those in Ijebu North. Adequate information on ACT needs to be made available and accessible under a public-private partnership if 2010 RBM targets (now past) and the 2015 Millennium Development Goal (ongoing) for malaria are to be realized in the study communities and Ogun state in general.